Adductor Canal Block versus Femoral Nerve Block for Pain Control After Anterior Cruciate Ligament Reconstruction: A Prospective Randomized Trial. Issue 7 (29th July 2019) - Okoroha, Kelechi R.; Lynch, Jonathan; Lizzio, Vincent; Yu, Charles Cong; Jildeh, Toufic Raja; Moutzouros, Vasilios
Objectives: Regional anesthesia in the form of a femoral nerve block (FNB) is a commonly performed technique that has been proven to provide effective analgesia following anterior cruciate ligament (ACL) reconstruction. The adductor canal nerve block (ANB) employs a similar sensory block around the knee while avoiding motor blockade of the quadriceps. The purpose of our study was to compare the efficacy of FNB versus ANB for pain control following ACL reconstruction. Our hypothesis was that there would be no difference in pain levels or opioid requirements between the two groups. Methods: We performed a prospective, double-blinded, randomized controlled trial. Sixty patients undergoing primary ACL reconstruction using bone-tendon-bone autograft were randomized to receive either an ANB or FNB preoperatively. The primary outcomes assessed were pain levels (visual analog scale) and narcotic requirements for 4 days following surgery. Secondary outcomes included ability to perform a straight leg raise in the recovery room and difference in thigh circumference between the operative and nonoperative leg measured at 7 days postoperatively. Results: Morphine requirements were less in ACB in the first 4 hours postoperatively (p = .02). Aside from this time interval, there were no differences between the 2 groups with regard to opioid requirements and pain scores at any other time. Similarly, no differences were noted in the patient's ability to perform a straight leg raise in the recovery room (p = .13) or in thigh circumference at the first postoperative visit (p = .09) Conclusion: The results of our study suggest similar efficacy in perioperative pain control with the use of an ANB for ACL reconstruction when compared to FNB. The potential long-term benefit of quadriceps preservation with the ACB is worthy of future study.